Case managers’ reflections of a brief case management intervention in Canada - Duncan, Andrea; Kirst, Maritt; Dainty, Katie N.; Wodchis, Walter P.; Stergiopoulos, Vicky (Frontiers in Psychiatry, 2023)
Introduction As demand for intensive case management services continues to outpace supply, community mental health agencies in Toronto, Ontario, introduced Short-Term Case Management (STCM). Objective This study sought to explore case managers’ perspectives and experiences with this new service delivery model. Methods Focus groups were conducted with twenty-one case managers, and transcripts analyzed using thematic analysis. Results Emerging themes suggest that despite embracing a recovery approach, case managers expressed mixed views on the acceptability and appropriateness of this service delivery model as an intervention. Conclusion The ideal population for this intervention are adults with mental health issues in need of system navigation, and those motivated to address their goals. Further research is needed to establish fidelity criteria.